Pemanfaatan Media Pembelajaran Berbasis Canva Terhadap Konsentrasi Belajar Siswa Di Sekolah Dasar - Shinta Alvy Rizqiyana; Bagas Mukti Nasrowi (Advances In Education Journal, 2026)
The role of teachers in education is crucial, as a nation's progress depends on their influence. The nation's future generations need quality education through a robust education system and competent teachers. The purpose of this study is to measure the impact of Canva on student concentration and to provide recommendations for appropriate digital media implementation for teachers to make the learning process more effective, engaging, and able to improve the quality of student attention and overall learning outcomes. This study utilized a library research method with a qualitative approach. Data analysis techniques employed were data analysis. Canva can be used as an alternative medium during digital learning that is relevant to supporting the improvement of elementary school students' concentration, particularly in science and science learning.